High-risk human papilloma virus in squamous cell esophageal cancer: a retrospective clinicopathologicalstudy from 2003 to 2006 in Edgardo Rebagliati-Martins Hospital, EsSalud, Lima, Peru - Beltran Gárate, Brady (2009)
Introduction: Human papilloma virus (HPV) is an agent involved in the pathophysiology of cervical cancer. Many reports describe an association between HPV and esophageal squamous-cell carcinoma (ESCC).Objective: The main objective of the study is to determine the frequency of high-risk HPV infection and ESCC.Material and method: A retrospective study including 29 ESCC cases with a histological and pathological diagnosis from 2003 to 2006 in Edgardo Rebagliati-Martins Hospital in Lima, Peru. Paraffin-embedded tissue fragments underwent RT-PCR tests for detecting HPV types 16, 18, 31, 33, and 45.Results: Mean age of patients was 73 years, male to female ratio was 3. Stage I disease was found in one case; stage II disease in 12 cases, stage III disease in 14 cases, and stage IV in 2. No highrigh HPV was found in any of the samples studied, even though we used two different probes.Conclusion: HPV was not detected in ESCC in the population studied.